2019
DOI: 10.4088/jcp.19m12928
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2, Randomized, Double-Blind, Placebo-Controlled Study of Adjunctive Pimavanserin in Patients With Major Depressive Disorder and an Inadequate Response to Therapy (CLARITY)

Abstract: Objective: Pimavanserin is a 5-hydroxytryptamine-2A antagonist and inverse receptor agonist. This phase 2 study examined the efficacy and safety of pimavanserin as adjunctive therapy in patients with major depressive disorder (MDD). Methods: This was a multicenter, randomized, double-blind, placebo-controlled study in patients with DSM-5-defined MDD and an inadequate response to a selective serotonin reuptake inhibitor (SSRI) or serotonin-norepinephrine reuptake inhibitor (SNRI). Using a 2-stage sequential par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 24 publications
4
62
0
Order By: Relevance
“…In the primary study, 207 patients were randomized at 27 study sites between December 2016 and October 2018 (Figure 1). At baseline, treatment groups were generally comparable for demographic and clinical characteristics (Fava et al, 2019). A greater proportion of patients in the pimavanserin group had a HAMD‐17 total score ≥24 (40.4% vs. 32.3%) and a CGI‐S score of 5 (markedly ill) or 6 (severely ill; 48.1% vs. 38.7%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the primary study, 207 patients were randomized at 27 study sites between December 2016 and October 2018 (Figure 1). At baseline, treatment groups were generally comparable for demographic and clinical characteristics (Fava et al, 2019). A greater proportion of patients in the pimavanserin group had a HAMD‐17 total score ≥24 (40.4% vs. 32.3%) and a CGI‐S score of 5 (markedly ill) or 6 (severely ill; 48.1% vs. 38.7%).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the study methodology was previously published (Fava et al, 2019). In brief, this was a multicenter, randomized, double‐blind, and placebo‐controlled study in patients with MDD and inadequate responses to treatment with a SSRI or SNRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the functional interactions in corticothalamic circuitry between 5-HT2A and mGlu2 receptors on DOI-induced head twitches and DRL 72-s behavior (Benneyworth et al, 2007;Gewirtz and Marek, 2000;Marek et al, 2001;Marek et al, 2000), we also tested the effects of LY354740 alone and together with the SSRI fluoxetine since 5-HT2A receptor antagonists enhance the antidepressant-like effects of fluoxetine or the tricyclic antidepressant desipramine (Marek et al, 2005;Ardayfio et al, 2008). These positive preclinical effects of 5-HT2A receptor antagonists and SSRIs have recently been translated to treatment-refractory patients with MDD (Fava et al, 2019). LY354740 failed to exert robust antidepressant-like effects when administered alone or even when administered in combination with selective serotonin reuptake inhibitor fluoxetine.…”
mentioning
confidence: 99%
“…Pimavanserin is approved in the United States by the Food and Drug Administration for treating hallucinations and delusions in patients with Parkinson’s disease psychosis. In a phase 2, randomized, placebo-controlled study (CLARITY), adjunctive pimavanserin demonstrated a significant improvement of depressive symptoms in patients with MDD and an inadequate response to previous treatment ( Fava et al ., 2019 ). This was a post hoc analysis of CLARITY was undertaken to evaluate the effects of adjunctive pimavanserin vs. placebo in a subgroup of patients with MDD and a baseline score ≥7 on the six-item HAMD-17 anxiety/somatization factor.…”
Section: Introductionmentioning
confidence: 99%